Between engagement and counter-hedging: China's India strategy. (3rd July 2019) - Jikang, Mao; Mingjiang, Li
ABSTRACT: From China's perspective, border disputes, India's strategic cooperation with other major powers and security competition between China and India in IOR are the main factors shaping Sino-India relations. China believes that border disputes is difficult to resolve but largely manageable, India is wary of joining forces with US and other major powers to contain China, and the two countries can still seek coexistence in IOR even though India is concerned about China's growing influence in this region. China is implementing a counter-hedging strategy towards India that features active engagement with India on one hand and a certain level of security pressures on India on the other hand. To prevent these three problems from becoming more serious and exacerbating the Sino-Indian contradiction, China find it necessary to pay more attention on engagement with India and come up with more diplomatic resources and policy inputs in handling the bilateral relations.